O cinema documentário de Miguel Mirra e o movimento de documentaristas: o cinema junto aos oprimidos - Orcasitas Pacheco, Luis Jorge (2018)
The present work is an approach to the trajectory and documentary work of Miguel Mirra, Argentine filmmaker who has developed several works in the field of communication and audiovisual production, motivated by the action of social movements that have been formed in his country during the last three decades. In this context, it is proposed to investigate and analyze the methods, concepts and ways in which this director structures a type of social and political documentary film, whose objective is to make visible and be in solidarity with the oppressed, the excluded and the exploited peoples. Based on a referential framework with historical, political, economic, argumentative and stylistic components, the project provides a reflective analytical of the cinematographic, cultural and ideological proposals of Miguel Mirra, whose documentary film is an immediate reflection of the cinematographic movements that emerged in Argentina. From the second half of the twentieth century, they have aimed to project a distinctive point of view, in order to generate alternative visions and new spheres of the public.